2023
DOI: 10.1186/s13578-023-01148-7
|View full text |Cite
|
Sign up to set email alerts
|

SHMT2 regulates esophageal cancer cell progression and immune Escape by mediating m6A modification of c-myc

Zhe Qiao,
Yu Li,
Yao Cheng
et al.

Abstract: Background In recent years, the role of altered cellular metabolism in tumor progression has attracted widespread attention. Related metabolic enzymes have also been considered as potential cancer therapeutic targets. Serine hydroxymethyltransferase 2 (SHMT2) has been reported to be upregulated in several cancers and associated with poor prognosis. However, there are few studies of SHMT2 in esophageal cancer (EC), and the related functions and mechanisms also need to be further explored. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…As reported, c-Myc, acting as popular transcription factor, was abnormally expressed in multiple human cancers and involved in regulating cell behaviors including cell proliferation, stemness, apoptosis, angiogenesis and metabolism through regulating its target genes, thereby facilitating tumor malignant progression [ 45 47 ]. Zhe et al revealed that SHMT2 accelerating esophageal cancer development through enhancing c-Myc m6A modification and its expression [ 48 ]. LncRNA GLCC1 promoted colorectal cancer cell proliferation, glycolysis by enhancing c-Myc stabilization through suppressing c-Myc ubiquitination via binding to HSP90 [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…As reported, c-Myc, acting as popular transcription factor, was abnormally expressed in multiple human cancers and involved in regulating cell behaviors including cell proliferation, stemness, apoptosis, angiogenesis and metabolism through regulating its target genes, thereby facilitating tumor malignant progression [ 45 47 ]. Zhe et al revealed that SHMT2 accelerating esophageal cancer development through enhancing c-Myc m6A modification and its expression [ 48 ]. LncRNA GLCC1 promoted colorectal cancer cell proliferation, glycolysis by enhancing c-Myc stabilization through suppressing c-Myc ubiquitination via binding to HSP90 [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, METTL3 is known to augment the immunosuppressive abilities of tumor-infiltrating myeloid cells [ 304 ]. In the context of EC, Serine hydroxymethyltransferase 2 (SHMT2) utilizes the METTL3/FTO/ALKBH5/IGF2BP2 pathway to mediate immune evasion by modifying c-myc through m6A [ 305 ]. These findings further indicate that IGF2BP3 plays a crucial role in the regulation of PD-1/PD-L1 degradation and impacts tumor immune responses.…”
Section: Classification Of Rna Methylationmentioning
confidence: 99%